Perluasan Makna Nomina Bahasa Indonesia dalam Novel - Fathia Roifah; Nguman Abdul Manaf (Universitas Mulawarman, 2023)
This research is based on the phenomenon of language development. This development results in language changes both in terms of words and meanings. This study aims to explain Indonesian nouns that experience meaning expansion in novels and explain the factors that cause the expansion of the meaning of Indonesian nouns in novels. This research uses a descriptive qualitative method. The data source of this research is novels from several authors, namely